Analysis of E-Advertising on Sales - Tatik Rohmawati; Senny Luckyardi (Journal of Business and Behavioural Entrepreneurship, 2021)
The purpose of this research is to analyse the increase in product sales using social media advertising. The research was conducted using literature study method and questionnaires that distributed to sellers who used social media advertising in marketing their products. The results show that selling products on social media using advertisements can generate more sales and cunsomers. With social media advertising, sellers can choose the type of potential customers according to the product being sold. The sellers can determine the type of prospective customer based on thier age, residence, and/or hobbies to it easier for the seller to divert the sale of their product. Therefore, social media advertising helps sellers who market their products to generate more sales.